Production process of cold-pressed edge-paralysis-preventing plywood
By controlling the moisture content of wood in the plywood cold pressing process and using high-performance adhesive formulas, and applying vibration assistance during the cold pressing process, the plywood edge problem is solved, the bonding strength and product quality are improved, and the edge cracking is reduced and shedding, improving production efficiency and appearance quality.
Patent Information
- Application Number
- CN202411040362.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-31
AI Technical Summary
A common problem in the cold pressing process of plywood is paralyzed edges, which causes the edges of the sheet to fail to meet the expected hardness and density, which are prone to deformation, cracking or warping, affecting strength, beauty, service life and safety.
By controlling the wood moisture content between 8% and 12%, high-performance adhesive formulations such as phenolic resin, urea-formaldehyde resin, nanocellulose and flexible polymers are adopted, and double-sided adhesive coating and cross-blank formation technology is adopted, and the cold Vibration assistance is applied during the pressure process to control pressure, time and temperature, and is divided into initial, boost and final pressure stages to ensure uniform penetration and dispersion of the adhesive.
It significantly improves the bonding strength of plywood, reduces the phenomenon of paralysis, improves the appearance quality and service life of the product, and ensures the consistency of production efficiency and product quality.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cold pressing process of plywood, and in particular relates to a production process of cold pressing anti-collapsed edge plywood. Background Art
[0002] The cold pressing process of plywood is a method in which the glue-coated substrate and veneer are neatly placed in a press for press gluing until the glue layer solidifies into a solid covering board. The characteristics of this process are simple equipment, easy operation, and no special facilities are required. However, it also has some limitations, especially the relatively long production cycle, which is more suitable for small batch production. In the cold pressing process, the key process parameters include pressure, time, temperature and the choice of adhesive. Usually, the cold pressing time is determined according to the thickness of the board and the curing speed of the adhesive, generally between 4 and 12 hours. In addition, although the cold pressing process usually does not involve additional heating steps, the ambient temperature also has a certain effect on the curing of the adhesive and the quality of the board. Edge collapse is a common and serious problem in the cold pressing production process of plywood, especially in the cold pressing process. Edge collapse mainly refers to the failure of the edge part of the board to achieve the expected hardness and density, resulting in the edge being easily deformed, cracked or warped. This phenomenon has a significant negative impact on the quality and performance of plywood: First, reduced strength: edge collapse significantly reduces the overall strength of the board, making it more susceptible to damage when subjected to external forces. Secondly, it affects the appearance: the collapsed edge usually causes the edge of the board to be uneven, affecting the appearance and texture of the product. Thirdly, it reduces the service life: due to the insufficient density and hardness of the collapsed edge, the wear resistance and corrosion resistance of this area will be reduced, thus shortening the service life of the plywood. Fourthly, it is a safety hazard: in certain applications, such as furniture or building structures, the collapsed edge may cause structural instability and pose a safety hazard. In order to avoid quality problems such as collapsed edges, various parameters need to be strictly controlled in the cold pressing process. Summary of the invention
[0003] Technical problem to be solved: Aiming at the edge collapse problem existing in the existing cold pressing process of plywood, the present invention provides a cold pressing anti-edge collapse plywood production process.
[0004] Technical solution: Cold-pressed anti-collapse plywood production process, the preparation steps are as follows: a. Use wood as the base material of plywood, and control the moisture content of wood between 8% and 12%; b. Prepare adhesive according to the following mass parts: 50-60 parts of phenolic resin, 30-40 parts of urea-formaldehyde resin, 1-3 parts of nanocellulose, 2-5 parts of flexible polymer, and 0.5-1.5 parts of cross-linking agent; c. Gluing and assembly: Use double-sided gluing to ensure that the glue layer evenly covers the wood surface, and the glue amount on each side is controlled at 200-250g / m 2; Cross-assembly is adopted, that is, the wood grain directions of two adjacent layers are perpendicular to each other, so as to improve the stability and deformation resistance of the board; d. Cold pressing treatment: The cold pressing pressure is controlled between 1.2-1.8MPa, the pressing time is set to 12-24 hours, the pressing environment temperature is 20-25℃, the humidity is 45%-55%, and vibration assistance is implemented during the pressing process; e. Decompression and removal: After the pressing is completed, the pressure is released and the plywood is carefully removed.
[0005] The above-mentioned wood is fir or pine.
[0006] Preferably, the adhesive comprises 55-58 parts of phenolic resin, 32-35 parts of urea-formaldehyde resin, 1.5-2.5 parts of nanocellulose, 3-4 parts of flexible polymer, and 0.8-1.2 parts of cross-linking agent.
[0007] Preferably, the phenolic resin is a thermosetting phenolic resin with a degree of polymerization between 500-1000; the urea-formaldehyde resin is an environmentally friendly urea-formaldehyde resin with low formaldehyde release, and its free formaldehyde content is less than 0.3%; the length of the nanocellulose is 50-100 nanometers and the diameter is 5-20 nanometers; the flexible polymer is a polyether or polyester flexible polymer with a molecular weight between 5000-20000; and the cross-linking agent is a multifunctional epoxy resin or an isocyanate cross-linking agent.
[0008] Preferably, the parameters of the cold pressing treatment are: the pressure is controlled between 1.4-1.6 MPa, the pressing time is set to 16-20 hours, the ambient temperature is controlled at 22-24° C., and the humidity is controlled at 48%-52%.
[0009] The specific pressing process is as follows: initial stage: start pressing with a pressure of 0.5-0.8MPa, and the duration is 20%-30% of the total pressing time; pressure increase stage: increase the pressure to 1.4-1.5MPa, and the duration is 40%-50% of the total pressing time; final pressure stage: during the remaining part of the pressing time, increase the pressure to 1.6MPa.
[0010] During the above pressure relief, the pressure is relieved at a rate of 0.1-0.2MPa per minute, and the duration is 10-20 minutes; during the pressure relief process, the temperature and humidity of the pressing environment are kept stable, the temperature is controlled at 20-25°C, and the humidity is maintained at 45%-55%.
[0011] Frequency of the above vibration: micro-vibration is applied during the pressurization stage and the final pressing stage, and the vibration frequency is controlled between 10-50 Hz to promote the penetration and dispersion of the adhesive in the wood fibers; vibration amplitude: the vibration amplitude of the micro-vibration is controlled between 0.1-0.5 mm to avoid excessive mechanical stress on the board; vibration time: micro-vibration is applied within the last 10-15 minutes of each pressing stage to ensure that the adhesive fully penetrates into the wood fibers and forms a good bond.
[0012] Beneficial effects: First, the process significantly improves the bond strength of plywood. Through the carefully selected adhesive formula, including high-performance compounds such as thermosetting phenolic resin, low formaldehyde-releasing urea-formaldehyde resin, and nanocellulose, a strong bond is formed between the layers of the board. This not only enhances the overall structural stability of the board, but also extends its service life. Secondly, the process effectively reduces the edge collapse phenomenon. By reasonably controlling the moisture content of the wood and applying micro-vibration during the cold pressing process, the penetration and dispersion of the adhesive in the wood fiber are promoted. This bonding method that penetrates deep into the wood fiber greatly reduces the cracking and falling off of the edge of the board, thereby improving the appearance quality and practicality of the product. Furthermore, through the refined cold pressing steps, including the initial stage, the boost stage, and the final pressing stage, as well as the precisely controlled pressure, time, and vibration conditions in each stage, it is ensured that the adhesive can penetrate into the wood evenly and deeply. This refined operation not only improves production efficiency, but also ensures the consistency and reliability of product quality. Finally, through specific data testing, such as bonding strength testing, edge width measurement and adhesive layer penetration depth testing, the performance of the product can be quantitatively evaluated, providing manufacturers with clear quality control indicators and consumers with reliable product quality assurance. DETAILED DESCRIPTION
[0013] The present invention is described in more detail below through examples.
[0014] Example 1
[0015] Select fir as the base material, and control its moisture content to 10%. Prepare adhesive: phenolic resin (thermosetting, polymerization degree 700): 55 parts; urea-formaldehyde resin (low formaldehyde release, free formaldehyde content 0.25%): 35 parts; nanocellulose (length 70 nanometers, diameter 15 nanometers): 2 parts; flexible polymer (polyether, molecular weight 15000): 4 parts; cross-linking agent (multifunctional epoxy resin): 1 part. Double-sided glue is used, and the glue amount on each side is 220g / m 2, and cross-assembly was adopted. The cold pressing treatment parameters were pressure of 1.5MPa, pressing time of 18 hours, ambient temperature of 23℃, humidity of 50%, and micro-vibration was applied during the pressure increase and final pressure stages, with a vibration frequency of 30 Hz and a vibration amplitude of 0.3 mm. Initial stage: Pressing started with a pressure of 0.6MPa, and the duration was 25% of the total pressing time (18 hours), that is, 4.5 hours. No vibration was applied at this stage. Pressure increase stage: The pressure was gradually increased to 1.5MPa, and the duration was 45% of the total pressing time, that is, 8.1 hours. Micro-vibration was applied at this stage, with a vibration frequency of 30 Hz, a vibration amplitude of 0.3 mm, and vibration for 5 minutes every 30 minutes. Final pressure stage: During the remaining part of the pressing time (5.4 hours), the pressure was increased to 1.6MPa. Continue to apply micro-vibration, with the same parameters as the pressure increase stage. Then the pressure was relieved at a rate of 0.15MPa per minute for 15 minutes, while maintaining an ambient temperature of 23℃ and a humidity of 50%.
[0016] Detection
[0017] Bond strength test, steps: Sample preparation: Cut a specimen of standard size from the plywood (length × width × thickness is 100mm × 25mm × actual thickness). Conditioning: Make sure the specimen reaches a balanced state before testing to avoid excessive moisture or excessive dryness. Clamp the specimen: Clamp both ends of the specimen in the fixture of the testing machine to ensure that the center of the specimen is aligned with the axis of the fixture. Loading and testing: Apply tension to the specimen at a constant speed (10MPa / min) until the specimen is destroyed. Record data: Record the maximum failure load and calculate the bond strength of 12.5MPa based on the specimen size.
[0018] Bond strength calculation formula: Bond strength = maximum failure load / (specimen width × specimen shear section length)
[0019] Steps for measuring the width of the slump edge: Sample preparation: Select a representative plywood sample. Observation and marking: Observe the edge of the plywood and mark the range of the slump edge. Measurement: Use a precise caliper or measuring instrument to measure the maximum width of the slump edge. Record data: Record the measured slump edge width of 0.2mm.
[0020] Glue penetration depth test steps: Sample preparation: Cut a small sample from the plywood to ensure that the complete glue layer is included. Mounting and polishing: Mount the sample in resin and then polish until the interface between the glue layer and the wood can be clearly seen. Observation and measurement: Observe the interface between the glue layer and the wood under a microscope and measure the depth of the glue layer penetrating into the wood. Record data: Record the maximum depth of glue layer penetration of 120μm.
[0021] Example 2
[0022] The steps are the same as in Example 1, but the vibration frequency is changed to 10 Hz. Effect test data: bonding strength (MPa): 9.8; edge width (mm): 0.4; adhesive layer penetration depth (μm): 100; the plywood has high bonding strength, slight edge collapse, low vibration frequency, and average adhesive penetration effect.
[0023] Example 3
[0024] The steps are the same as in Example 1, but vibration is not applied. Effect test data: bonding strength (MPa): 9.0; edge collapse width (mm): 0.7; adhesive layer penetration depth (μm): 80; Effect: The plywood bonding strength is average, with obvious edge collapse, without vibration assistance, the adhesive penetration effect is not good.
[0025] Example 4
[0026] The steps are the same as in Example 1, but the cold pressing time is changed to 12 hours. Effect: Due to the short pressing time, the plywood bonding strength is relatively low at 7.0 MPa, with a 1.0 mm edge collapse phenomenon. Despite the vibration assistance, insufficient time leads to incomplete adhesive penetration of 85 μm.
[0027] Example 5
[0028] The steps are the same as in Example 1, but the wood moisture content is controlled to 15%, which exceeds the specified range. Effect: The plywood bonding strength is 5.0 MPa low, and the edge collapse phenomenon is 2.0 mm serious. The high wood moisture content affects the bonding effect of the adhesive, which is difficult to improve even with vibration assistance.
[0029] Effect comparison
[0030] By comparing the above five embodiments, it can be seen that the effect of embodiment 1 is the best. Reasonable vibration frequency and time significantly improve the penetration and dispersion effect of the adhesive in the wood fiber, thereby enhancing the bonding strength of the plywood and reducing the edge collapse phenomenon. The effect of embodiment 2 is second to none due to the low vibration frequency. The effect of embodiment 3 is further reduced due to the lack of vibration. The penetration effect of the adhesive is affected in embodiment 4 due to the short pressing time. In embodiment 5, the quality of the plywood is seriously affected due to the high moisture content of the wood. Therefore, in the production process of cold-pressed anti-edge collapse plywood, reasonable control of vibration parameters, pressing time and wood moisture content is a key factor.
[0031] The above embodiments are only used to illustrate the contents of the present invention rather than to limit the present invention. Therefore, any changes within the meaning and scope equivalent to the claims of the present invention should be considered to be included in the scope of the claims.
Claims
1. The production process of cold-pressed anti-collapse edge plywood is characterized by: The preparation steps are as follows: a. Use wood as the base material of plywood and control the moisture content of the wood between 8% and 12%; b. Prepare the adhesive according to the following mass parts: 50-60 parts of phenolic resin, 30-40 parts of urea-formaldehyde resin, 1-3 parts of nanocellulose, 2-5 parts of flexible polymer, and 0.5-1.5 parts of cross-linking agent; c. Gluing and assembly: Double-sided gluing is adopted to ensure that the glue layer evenly covers the wood surface, and the glue coating amount on each side is controlled at 200-250g / m²; cross assembly is adopted, that is, the wood grain directions of two adjacent layers are perpendicular to each other, so as to improve the stability and deformation resistance of the board; d. Cold pressing treatment: The cold pressing pressure is controlled between 1.2-1.8MPa, the pressing time is set to 12-24 hours, the pressing environment temperature is 20-25℃, the humidity is 45%-55%, and vibration assistance is implemented during the pressing process; e. Decompression and removal: After the pressing is completed, the pressure is released and the plywood is taken out.
2. The cold-pressed anti-collapse edge plywood production process according to claim 1 is characterized in that: The wood is fir or pine.
3. The cold-pressed anti-collapse edge plywood production process according to claim 1 is characterized in that: The adhesive is specifically composed of: 55-58 parts of phenolic resin, 32-35 parts of urea-formaldehyde resin, 1.5-2.5 parts of nanocellulose, 3-4 parts of flexible polymer, and 0.8-1.2 parts of cross-linking agent.
4. The cold-pressed anti-collapse edge plywood production process according to claim 1 is characterized in that: The phenolic resin is a thermosetting phenolic resin with a degree of polymerization between 500 and 1000; the urea-formaldehyde resin is an environmentally friendly urea-formaldehyde resin with low formaldehyde release, and its free formaldehyde content is less than 0.3%; the length of the nanocellulose is 50-100 nanometers and the diameter is 5-20 nanometers; the flexible polymer is a polyether or polyester flexible polymer with a molecular weight between 5000 and 20000; and the crosslinking agent is a multifunctional epoxy resin or an isocyanate crosslinking agent.
5. The cold-pressed anti-collapse edge plywood production process according to claim 1 is characterized in that: The parameters of the cold pressing treatment are: the pressure is controlled between 1.4-1.6 MPa, the pressing time is set to 16-20 hours, the ambient temperature is controlled at 22-24° C., and the humidity is controlled at 48%-52%.
6. The cold-pressed anti-collapse edge plywood production process according to claim 5 is characterized in that: Initial stage: start pressing with a pressure of 0.5-0.8MPa, which lasts for 20%-30% of the total pressing time; pressure increase stage: increase the pressure to 1.4-1.5MPa, which lasts for 40%-50% of the total pressing time; final pressure stage: increase the pressure to 1.6MPa during the remaining part of the pressing time.
7. The cold-pressed anti-collapse edge plywood production process according to claim 1 is characterized in that: During the pressure relief, the pressure is relieved at a rate of 0.1-0.2MPa per minute, and the duration is 10-20 minutes; during the pressure relief process, the temperature and humidity of the pressing environment are kept stable, the temperature is controlled at 20-25°C, and the humidity is maintained at 45%-55%.
8. The cold-pressed anti-collapse edge plywood production process according to claim 5 is characterized in that: The vibration frequency: micro-vibration is applied in the pressure-increasing stage and the final pressure stage, and the vibration frequency is controlled between 10-50 Hz; vibration amplitude: the vibration amplitude of micro-vibration is controlled between 0.1-0.5 mm; vibration time: micro-vibration is applied within the last 10-15 minutes of each pressing stage.
Citation Information
Patent Citations
Structure plywood plate for timber-construction and production method thereof
CN101456195A
Cold-pressed rapid gluing method for wood
CN104441098A
Water-based decoration panel base plate with zero-formaldehyde emission and production process thereof
CN106182219A
Cold-pressing production method for plywood
CN106738110A
Preparation method for cold pressed multilayer wood laminated timber
CN107243957A
